Cellular and molecular immunology - Abbas, Abul K.
"The top required and recommended immunology text worldwide, Cellular and Molecular Immunology by Drs. Abul K. Abbas, Andrew H.H. Lichtman, and Shiv Pillai, is a clear, well-written, and superbly illustrated introduction to the field. The 9th Edition retains a practical, clinical focus while updating and revising all content to ensure clarity and comprehension, bringing readers fully up to date with new and emerging information in this challenging area"--Publisher's description.